Relationship Between Circadian Strain, Light Exposure, and Body Mass Index in Rural and Urban Quilombola Communities - Constantino, Débora Barroggi; Xavier, Nicoli Bertuol; Levandovski, Rosa; Roenneberg, Till; Hidalgo, Maria Paz; Pilz, Luísa K. (Frontiers in Physiology, 2022)
Industrialization has greatly changed human lifestyle; work and leisure activities have been moved indoors, and artificial light has been used to illuminate the night. As cyclic environmental cues such as light and feeding become weak and/or irregular, endogenous circadian systems are increasingly being disrupted. These disruptions are associated with metabolic dysfunction, possibly contributing to increased rates of overweight and obesity worldwide. Here, we aimed to investigate how activity-rest rhythms, patterns of light exposure and levels of urbanization may be associated with body mass index in a sample of rural and urban Quilombola communities in southern Brazil. These are characterized as remaining social groups who resisted the slavery regime that prevailed in Brazil. Quilombola communities were classified into five groups according to their stage of urbanization: from rural areas with no access to electricity to highly urbanized communities. We collected anthropometric data to calculate body mass index, which was categorized as: ≥18.5 kg/m² to <25 kg/m² = normal weight; ≥25 kg/m² to <30 kg/m² = overweight; ≥30 kg/m² = obese. Subjects were asked about their sleep routines and light exposure on workdays and work-free days using the Munich Chronotype Questionnaire (N = 244 included). In addition, we analysed actimetry data from 121 participants with seven consecutive days of recordings. Living in more urbanized areas and higher intradaily variability of activity-rest rhythms were associated with an increased risk of belonging to the overweight/obese group, when controlling for age and sex. These findings are consistent with preclinical data and point to potential strategies in obesity prevention and promotion of healthy metabolic profiles.